2018
DOI: 10.1109/tcomm.2017.2782741
|View full text |Cite
|
Sign up to set email alerts
|

3GPP-Inspired HetNet Model Using Poisson Cluster Process: Sum-Product Functionals and Downlink Coverage

Abstract: The growing complexity of heterogeneous cellular networks (HetNets) has necessitated a variety of user and base station (BS) configurations to be considered for realistic performance evaluation and system design. This is directly reflected in the HetNet simulation models proposed by standardization bodies, such as the third generation partnership project (3GPP). Complementary to these simulation models, stochastic geometry-based approach, modeling the locations of the users and the K tiers of BSs as independen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
96
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(99 citation statements)
references
References 38 publications
3
96
0
Order By: Relevance
“…For HCNs with non-Poisson deployments, it is often the case that it is hard to perform an exact mathematical analysis of key performance metrics such as the SIR distribution (sometimes called the coverage probability). Even if an exact expression of the SIR distribution exists, it is available in a complex form that does not help gain insights about the performance of the network for different network parameters [11]- [15].…”
Section: B Related Workmentioning
confidence: 99%
“…For HCNs with non-Poisson deployments, it is often the case that it is hard to perform an exact mathematical analysis of key performance metrics such as the SIR distribution (sometimes called the coverage probability). Even if an exact expression of the SIR distribution exists, it is available in a complex form that does not help gain insights about the performance of the network for different network parameters [11]- [15].…”
Section: B Related Workmentioning
confidence: 99%
“…With some assumptions to the distribution (such as PPP) of the node locations, the system performance of a HetNet can be expressed by quickly computable integrals with a small number of parameters [14]. Recent studies have found that simply using a PPP based geometric model is not rich enough to analyze the increasingly complex HetNet, yet the Poisson cluster process (PCP) based analysis is more capable [15]. Some quantitative properties of PCP and PCP based device-to-device (D2D) network can be found in [15]- [18].…”
Section: B Related Work and Our Contributionsmentioning
confidence: 99%
“…Recent studies have found that simply using a PPP based geometric model is not rich enough to analyze the increasingly complex HetNet, yet the Poisson cluster process (PCP) based analysis is more capable [15]. Some quantitative properties of PCP and PCP based device-to-device (D2D) network can be found in [15]- [18]. Specifically, the coverage probabilities of several HetNet configurations based on the 3rd generation partnership project (3GPP) model were studied in [15].…”
Section: B Related Work and Our Contributionsmentioning
confidence: 99%
“…Although PPP is tractable in modeling random networks, it is not rich enough in capturing spatial coupling between UE and BS locations that exists in traffic hotspots [18], [19], which can be better modeled by Poisson cluster process (PCP). The PCP-based modeling and performance analysis of HetNet has gained much attention in these years [19]- [21].…”
Section: Introductionmentioning
confidence: 99%
“…The PCP-based modeling and performance analysis of HetNet has gained much attention in these years [19]- [21]. A complete characterization of the downlink coverage probability for a PCP-based HetNet model under max-SINR based association scheme is investigated in [18]. The BS-centric cellular network was analyzed in [22], in which the locations of BSs are modeled as a PPP, and the UEs are modeled as a PCP around BSs.…”
Section: Introductionmentioning
confidence: 99%